Characterization of the vicuña (Vicugna vicugna) fibre production in the Cusco Region, Perú - Pacheco C., Joel (2019)
This aim of this study was to describe the fibre diameter and fleece weight of vicuñas in the Cusco Region, Peru. The fibre diameter of 302 fibre samples of young, juveniles and adult vicuñas were evaluated using an OFDA 2000® equipment. The samples were collected in different programmed captures (called Chaccus) under two management systems: wildness and semi-captivity. In addition, 633 fleeces were weighed and differentiated by age, sex and type of management of the animals. The present study was authorized through the Resolution of General Direction N.° 180-2016-SERFOR/DGGSPFFS. The average fineness of the fibre of young (13.24 μm), juveniles (12.03 μm) and adults (12.72 μm) was determined. The fineness of fibre for males and females was 12.99 and 13.53 μm in young, 12.06 and 12.02 μm in juveniles and 12.88 and 12.58 μm in adults respectively. The smallest diameter of the fibre was found in juvenile vicuñas raised in the wildness (11.88 μm) and in the locality of Canllini (11.49 μm). The weight of fleece was greater in vicuñas raised in the wildness (165.01 g) and in adult animals (162.97 g), and without statistical differences between sexes. It is concluded that the best fibre characteristics were found in animals maintained in the wild.